Use of Rugae In Sex Determination: A Preliminary Study - Yaşar, Zehtiye Füsun; Pelin, İsmail Can; Büken, Erhan; Zengin, Hatice Yağmur; Kürkçüoğlu, Ayla; Dayangaç, Bülent; Koç, Fırat (The Bulletin of Legal Medicine, 2019)
Purpose: The purpose of this study is to examine the prevalence palatal ruga samples in terms of number, length, shape, association with the side branches and the direction of settlement aspects in the Anatolian population, and to question the usability of palatal rugae in sex determination of victims in forensic cases and in mass disasters.Materials and Methods:Rugae of upper jaw model belonging to 248 individuals were analyzed by using Thomas-Kotze and Closed classification system and statistical analysis of male and female rugae types was made during the study. For the evaluation of the data, SPSS (17.0) version and Pearson Chi-Square, Fisher’s Exact Test, Mannn-Whitney U analyses were used.Findings:During the study 2367 rugae from 132 (53.2%) females and 116 (46.8%) males were analyzed. As a result of the analyses, it was concluded that sex was not an effective factor on rugae number, that the total number of rugae varied between 6-15 in women, 5-18 in men and that there was no statistically meaningful difference (p=0.161) in distribution of rugae numbers between sex groups. Besides, it was determined that there is no meaningful correlation between rugae length and sex (p=0.526), between rugae shape and sex (p=0.672), between sex and adjunction shapes of rugae lateral branches (p=0.189) and between sex and rugae location directions (p=005).Conclusion:Based on the evaluation, the most frequently seen rugae types were determined to be the primary type with respect to length and curved type with respect to shape. Sexual dimorphism was not seen in any ...
Keywords: forensic odontology; mass disaster; palatal rugae; population characteristic